An energy‐efficient anti‐jam cognitive system for wireless OFDM communication. (29th May 2013) - Javed, I.; Loan, A.; Mahmood, W.
SUMMARY In this paper, anti‐jamming capabilities are proposed for a generic OFDM‐based wireless communication system. The performance of a wireless system may severely degrade in presence of jamming or intentional interferences. A malicious entity can send strong interference or noisy signals in the same transmit frequency band thus preventing the intended receiver to correctly decode the transmitted data. As a countermeasure, our work proposes algorithms and techniques to restore the system performance in presence of such malicious entities. Proposed anti‐jamming system consists of an adaptive framework that adapts itself to varying jammer behavior and wireless environment, and then, it chooses an optimal strategy to effectively cancel out the effect of jamming and channel fading. Optimization problem is formulated as a multi‐objective criterion for maximization of system throughput and minimization of energy consumption. Simulation results computed in Rayleigh fading channels with different wideband jamming modes and powers show that the proposed system effectively cancels out the jamming and channel fading effects thus maximizing the system performance and minimizing cost of energy consumption. Copyright © 2013 John Wiley & Sons, Ltd.